The Effect of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earnings per Share (EPS) on Stock Prices - Ravita Sherliana; Amru Usman; Iswadi; mardiaton Mardiaton; Sri Mulyati (Universitas Syiah Kuala, 2026)
This study is motivated by the research gap in understanding the influence of financial ratios on stock prices, particularly among companies included in the LQ45 index of the Indonesia Stock Exchange. Using a quantitative approach, 35 firms were selected through purposive sampling, resulting in 70 firm-year observations analyzed with panel data regression under the Random Effect Model. The findings indicate that Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) show no significant effect on stock prices, whereas Earnings per Share (EPS) exerts a positive and significant influence, underscoring its role as the primary determinant of stock valuation among LQ45 firms. The study is limited by its relatively short observation period and restricted sample, suggesting caution in generalizing the results. Practical implications highlight the importance of EPS as a key indicator for investors in decision-making, while firms are encouraged to strengthen financial reporting transparency to enhance market confidence. The originality of this research lies in providing recent empirical evidence on the decisive role of EPS in shaping stock prices in the Indonesian capital market, thereby enriching the literature on financial performance and investment behavior in emerging markets